Voices in Evidence-Based Newborn Care: A How-to-Guide on Developing a Parent-Facing Podcast - Parga-Belinkie, Joanna; Merchant, Raina M (JMIR Publications, 2019)
Podcasting is becoming a more popular form of media. Its use in medical education is being researched-but what about its use in public education? In this tutorial, the authors offer a how-to-guide on starting a public or patient-facing podcast. The authors hope to inspire more physicians to utilize this type of media to share evidence-based information. More research is needed looking into how podcasting can be used to help with patient education.